HUBUNGAN KEMAMPUAN MEMBACA DENGAN PRESTASI BELAJAR SISWA LAMBAT MEMBACA DI SDN 101775 SAMPALI - Anisa Jahro Pandiangan; Syahrial; Zainuddin; Halimatussakdiah; Edizal Hatmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT The problem of low reading ability among elementary school students is still frequently found and has an impact on difficulties in understanding learning materials, which in turn affects students’ learning achievement. This condition indicates that reading ability plays a very important role in supporting students’ academic success. Therefore, this study aims to determine the relationship between reading ability and the learning achievement of slow reading students at SDN 101775 Sampali. This study employed a quantitative approach with a correlational research design. Data were collected through a reading ability test as primary data and documentation of Mid-Semester Summative scores in Indonesian language as secondary data. The research instruments had been tested for content validity, empirical validity, and reliability to ensure their feasibility. The results showed that there is a significant relationship between reading ability and students’ learning achievement. This is proven by the Spearman correlation test which obtained a correlation coefficient of 0.793 with a significance value of 0.000 (p < 0.05). This result indicates that the relationship between the two variables is categorized as strong and significant. In conclusion, the higher the students’ reading ability, the higher their learning achievement. Therefore, improving reading ability should be a primary focus in efforts to enhance students’ academic performance. n